Ferroptosis Inhibitor Regulates the Disease Progression of Systematic Lupus Erythematosus Mice Model Through Th1/Th2 Ratio - Yang, Bo; Hou, Shihao; Huang, Shiqing; Li, Hongwen; Li, Yepeng (Current Molecular Medicine, 2023)
Background: Systematic lupus erythematosus (SLE) is an autoimmunemediated disease. So far, there is no relevant report on ferroptosis in SLE research, and the role of T helper 1 (Th1) and T helper 2 (Th2) cells in SLE is still unclear. Methods: This study employed SLE mice models with and without ferroptosis inhibitors (Liproxstatin128;‘1) and normal control mice. Treated mice were analyzed with hematoxylin and eosin (H) staining, immunohistochemical detection of glutathione peroxidase 4 (GPX4), malondialdehyde (MDA) detection, ELISA(enzyme-linked immunosorbent assay) detection of Th1 and Th2 cytokines and flow cytometry detection of Th1 and Th2 ratio. Results: The results showed that compared with the normal group, the SLE group exhibited significantly higher expression of anti-double-stranded deoxyribonucleic acid (anti-dsDNA), MDA and Th1 cytokines, significantly lower expression of GPX4 and Th2 cytokines and increased Th1/Th2 ratio. Similarly, compared with the SLE group, the SLE + liproxstatin-1 group showed significantly low expression of anti-dsDNA, MDA and Th1 cytokines, significantly high expression of GPX4 and Th2 cytokines and reduced Th1/Th2 ratio. Conclusion: These results demonstrate that ferroptosis may be involved in promoting SLE development. Therefore, inhibiting ferroptosis may be a potential treatment for SLE. Similarly, the Th1/Th2 ratio may have a role in promoting SLE development.
Keywords: mice model